On the phase analysis of multi-carrier signals for high-precision fault detection by reflectometry - Cabanillas, Esteban; Layer, Christophe; Kafal, Moussa (2017 IEEE SENSORS, 2017)
Electronic systems are becoming always more complex and consequently more subject to defect. For safety, security and integrity reasons, wire diagnosis is crucial. The emerging of sensor networks and connected objects has created the need for embedded and non invasive fault diagnosis solutions. Actual systems rely on multi-carrier reflectometry to locate upcoming defects on wires, though their precision stays within the physical limits of their components, especially the sampling frequency of their analog parts. We propose a new approach combining multi-carrier reflectometry and phase analysis to overcome this limit, in order to improve the precision of the localization of the defects on electrical wires. Based on an FPGA implementation, our novel method and the resulting system has proven a five-times better accuracy than state-of-the-art methods on the same platform.